2017
DOI: 10.1093/pasj/psx070
|View full text |Cite
|
Sign up to set email alerts
|

Two- and three-dimensional wide-field weak lensing mass maps from the Hyper Suprime-Cam Subaru Strategic Program S16A data

Abstract: We present wide-field (167 deg 2 ) weak lensing mass maps from the Hyper Supreme-Cam Subaru Strategic Program (HSC-SSP). We compare these weak lensing based dark matter maps with maps of the distribution of the stellar mass associated with luminous red galaxies. We find a strong correlation between these two maps with a correlation coefficient of ρ = 0.54 ± 0.03 (for a smoothing size of 8 ′ ). This correlation is detected even with a smaller smoothing scale of 2 ′ (ρ = 0.34 ± 0.01). This detection is made uniq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 66 publications
2
59
0
Order By: Relevance
“…Nevertheless, the observed distortion contains an additional scatter due to the shape measurement error. Following Oguri et al (2018) we simulate an "observed" distortion of each galaxy taking into account both the intrinsic shape and measurement error. We first rotate the distortion of individual galaxies obs and obtain the rotated distortion as ran = obs e iφ , where φ is a random number between 0 and 2π.…”
Section: Mock Cataloguesmentioning
confidence: 99%
“…Nevertheless, the observed distortion contains an additional scatter due to the shape measurement error. Following Oguri et al (2018) we simulate an "observed" distortion of each galaxy taking into account both the intrinsic shape and measurement error. We first rotate the distortion of individual galaxies obs and obtain the rotated distortion as ran = obs e iφ , where φ is a random number between 0 and 2π.…”
Section: Mock Cataloguesmentioning
confidence: 99%
“…We describe the estimator from convergence which is reconstructed by the shape of galaxies distorted (Oguri et al 2018). The gravitational lensing distorts the image of the source galaxies.…”
Section: Convergence Measurementioning
confidence: 99%
“…This can be identified as the reason for the formation of the large-scale structure in the universe. An alternative is to measure the precise CMB temperature in the region where dark matter is considered to exist [25,26]. The model predicts that the CMB temperature in that region is higher than elsewhere because larger values of G and m e can be identified as dark matter.…”
Section: Discussionmentioning
confidence: 99%